COMPLICATION ANALYSIS OF PEDIATRIC AND ADOLESCENT ACL RECONSTRUCTIONS IN THE ABOS DATABASE. Issue 3 (31st March 2019) - Ellis, Henry B.; Clarke, Claire; Sabatino, Meagan J.; Pennock, Andrew; Cruz, Aristides I.; Gauthier, Luke; Gerow, Frank; Ganley, Theodore J.; Jones, Kerwyn; Shea, Kevin
INTRODUCTION: Anterior cruciate ligament (ACL) reconstruction is one of the most common procedures performed in adolescents. Similarly, the rate of ACL reconstructions performed in pediatric patients has been increasing, and this population has the highest rate of primary and revision ACL Surgery. The purpose of this study was to review data on ACL reconstructions performed in patients under the age of 19 years that were submitted to the American Board of Orthopaedic Surgeons (ABOS) Part 2 examination to evaluate post-operative complications and trends over time in applicant fellowship training. METHODS: A query to the ABOS SCRIBE database was submitted for all ACL reconstructions performed in patients less than 19 years old. The database query was based on ICD-9 and ICD-10 diagnostic codes submitted by each applicant. Data included geographic region, fellowship training of the applicant, exam subspecialty, and reported complications. A subgroup analysis of complications was also performed in patients less than 15 years compared to those 15-18 and amongst different applicants based on fellowship training. RESULTS: From 2000 – 2016, 9, 767 ACL reconstructions were performed by candidates taking Part 2 of the ABOS board certification process. The mean age at surgery was 16 years (reported age range 0-18) and a meniscus procedure was performed in 57% of cases. There was a 41% increase in ACL reconstructions in those under the age of 15 years between 2000 and 2016. In each age group, the incidence of ACL reconstruction in males was higher than in females (ratio 5:4) except in those 12 and 13 years old whereby the incidence was higher in females (ratio 2:1). A majority (70.5%) of ACL reconstructions were performed by candidates with a sports medicine fellowship. In patients less than 15 years old 24.5% of reconstructions were performed by candidates with a pediatric or dual pediatric and sports medicine fellowship training. The overall complication rate was 13.6% with 0.4% anesthetic related complication (0.2% related to regional anesthesia). The reoperation rate was 0.8% and the readmission rate was 0.5%. Twelve patients (0.14%) sustained a venous thromboembolic event (6 deep vein thrombosis and 6 pulmonary embolism). A majority of complications (10.83%) were related to the surgery. The most common surgery related complications were infection (1.51%) and arthrofibrosis (1.3%). The overall incidence of reported complications was not statistically different between those with sports (13.7%), pediatric (16.3%), or both sports and pediatric fellowships (17.5%). Differences in specific complications were noted when comparing those with only pediatric training and those with only sports medicine fellowship training including graft related problems (1.9% vs. 0.7%, p=0.001, respectively) and nerve palsy/injury (1.9% vs. 0.6%, p<0.001, respectively). CONCLUSION/DISCUSSION: ACL reconstruction in the adolescent and pediatric age groups are primarily performed by candidates with a sports medicine fellowship. Complications rates between candidates reporting either sports medicine or pediatric fellowship training are overall comparable. Graft related complication and nerve palsy/injury were lower in those with sports medicine fellowships and both pediatric and sports medicine fellowships suggesting that additional training in sports medicine or arthroscopy may help minimize those complications. Longitudinal studies evaluating long term risks and complications after pediatric/adolescent ACL reconstruction are needed.